Cribriform colon cancer: a morphological growth pattern associated with extramural venous invasion, nodal metastases and microsatellite stability. Issue 7 (29th March 2021) - Taylor, Alexander S; Liu, Natalia; Fang, Jiayun M; Panarelli, Nicole; Zhao, Lili; Cheng, Jerome; Gopal, Purva; Hammer, Suntrea; Sun, Jing; Appelman, Henry; Westerhoff, Maria
Abstract : Background: Cribriform comedo-type adenocarcinoma was a colon cancer subtype recognised in the previous WHO classification of tumours that is no longer included in the recent edition. Previous reports have described colon cancers with cribriform growth as having worse overall survival and being associated with microsatellite stability. We sought to validate whether cribriform carcinoma (CC) is a distinct morphological subtype with clinical relevance in the context of modern colon cancer diagnosis. Methods: Consecutive cases of non-neoadjuvantly treated colon cancer resections were identified (n=177) and reviewed to evaluate for CC and other histopathological and clinical features. CC was defined as solid nests of cancer with round, 'punched out' spaces and intraluminal bridges, reminiscent of ductal carcinoma in situ of the breast. Results: CC was present in 18.6% of the consecutive case cohort. Compared with all other cases, CC was associated with positive lymph nodes, increased depth of invasion, extramural venous involvement (EMVI), and microsatellite stability, and was less likely to have tumour infiltrating lymphocytes (p<0.05). In contrast to previous reports, we did not find significantly worse overall, disease-specific or recurrence-free survival for CC. Morphological features mimicking CC occurred in 33.3% of all other colon cancer cases. Conclusion: Identifying CC may be useful due to its association with worse stage at presentation and EMVI, but given that cribriform-like appearance may be found in many colon cancer cases and that we did not find a survival difference for CC, CC may not necessitate its own subtype classification.